2007
DOI: 10.1071/wr06123
|View full text |Cite
|
Sign up to set email alerts
|

Use of Xanthorrhoea semiplana (grass-trees) for refuge by Rattus fuscipes (southern bush rat)

Abstract: This study investigated the use of the grass-tree, Xanthorrhoea semiplana F.Muell. (family Xanthorrhoeaceae), for shelter by Rattus fuscipes (southern bush rat) in South Australia. Eight bush rats were radiotracked for 4-8 days each. To identify the understorey shelters available to each animal, surveys were conducted using point-intercept sampling at 2-m intervals along transect lines. Grass-tree density was calculated in each area used by the radio-tracked animals, and canopy thickness of grass-trees selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…To support this idea, our study found that much of the utilisation of grasstrees in the 5-and 14-year burn sites involved movement through one grasstree skirt to another, and the erratic and convoluted trails beneath and among skirts of grasstrees suggested that foraging was taking place (Anderson et al 1988;Stokes et al 2004). The importance of grasstrees as habitat is also likely to vary with the amount of other understorey cover present (Frazer and Petit 2007) and in areas where logs and other forms of understorey cover are sparse or absent (such as open woodlands) grasstrees are more likely to be a critical habitat component for mardos. The importance of managing fire to retain grasstree skirts and crowns will, therefore, vary between habitats.…”
Section: Do Mardos Utilise Grasstrees As Foraging or Nesting Sites?mentioning
confidence: 72%
“…To support this idea, our study found that much of the utilisation of grasstrees in the 5-and 14-year burn sites involved movement through one grasstree skirt to another, and the erratic and convoluted trails beneath and among skirts of grasstrees suggested that foraging was taking place (Anderson et al 1988;Stokes et al 2004). The importance of grasstrees as habitat is also likely to vary with the amount of other understorey cover present (Frazer and Petit 2007) and in areas where logs and other forms of understorey cover are sparse or absent (such as open woodlands) grasstrees are more likely to be a critical habitat component for mardos. The importance of managing fire to retain grasstree skirts and crowns will, therefore, vary between habitats.…”
Section: Do Mardos Utilise Grasstrees As Foraging or Nesting Sites?mentioning
confidence: 72%
“…Over half (61 of 107) of the species analysed had a significant ( P < 0.05) indicator value for a particular community, indicating that the classification encompassed a large proportion of variation in the vegetation. A number of the species with high indicator values are of particular interest to management, including species of Xanthorrhoea , which provide key habitat to plants and animals (Petit & Dickson ; Frazer & Petit ; Swinburn et al. ) and Leptospermum continentale and Pteridium esculentum , which are important fire fuel elements (McCarthy et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that an increasing T a could have made active arousal easier by reducing the T b -T a differential, especially during the earlier phase of rewarming. We think it highly unlikely the animal was exposed to direct solar radiation, because bush rats normally use underground burrows or ground nests under dense grass trees (Collins 1973 ; Frazer and Petit 2007 ). Basking in the sun should also have led to faster rewarming rates than those recorded.…”
Section: Discussionmentioning
confidence: 99%